AB0815 Prevalence of dorsal and lumbar vertebral osteoarthritis in women over 50 years of age evaluated using the lane radiographic score in five latin-american countries. (15th June 2017) - Carrillo, SM; Xibillé, DX; Granados-Sandoval, E; Curiel-Quiroz, D; Denova-Gutierrez, E; Olvera-Soto, MG; Clark, P
Abstract : Background: Osteoarthritis is the most common musculoskeletal disease worldwide. Spinal osteoarthritis (OA) is a frequent cause of back pain and disability in patients over 60. The frequency of radiographically-evident dorsal and lumbar OA in Latin America is unknown Objectives: To determine the prevalence of dorsal and lumbar vertebral OA in a database-driven random sample of women 50 years of age and older from the Latin-American Vertebral Osteoporosis Study (LAVOS) in 5 LA countries (México, Brazil, Argentina, Colombia and Puerto Rico) Methods: Lumbar and Dorsal X-rays were performed per a standardized protocol and analyzed independently by two trained radiologists and a general practitioner using the Lane score to establish diagnosis and degree of vertebral OA severity. Inter and intra observer agreement was determined to be k>0.6. Descriptive statistics were used to analyze demographic variables. Prevalence was determined using means and standard deviations for quantitative variables and simple frequencies and percentages for qualitative variables. Bivariate analysis was performed to associate age, BMI and other variables with the presence of OA, using c 2 and the magnitude of association through OR and 95% CI, carrying out a multivariate analysis to adjust the frequency of OA to other variables Results: 405 women, mean age 69.4 (58–80), median weight 64 kg (56.9–73.4) mean height 151.8 cm (±7.6) were analyzed. 5.65% were underweight, 21% had normal weight, 41.6% were overweight and 31.5% were obese. Argentina contributed 19% of the sample, Brazil 14.8%, Colombia 20.1%, México 33.3% and Puerto Rico 12.8%. OA prevalence per age group was 76.3% (95% CI 68.4–84.2) in those 50–59, 83.8% (95% CI76.6–91.2) in those 60–69, 84.3% (95% CI 76.7–91.7) in those 70–79 and 94.9% (95% CI 90.4–99.3) in those 80 or older (p=0.003). Prevalence per country was as follows: Brazil 93%, Colombia 90%, México 85%, Puerto Rico 79% and Argentina 74%. Prevalence per BMI was 80% in normal weight, 82.5% in overweight and 87.5% in obese. 72.6% of sampled women had dorsal OA (Argentina 48.1%, Brazil 65%, Puerto Rico 73.1%, México 79.3%, Colombia 90.1%). Obesity was a risk factor for the development of dorsal OA (OR 2.46) when compared to normal BMI (p=0.01). Lumbar OA was found in 44.9% of the sampled women (Argentina 68.8%, Brazil 65%, Colombia and Puerto Rico 42.3% each, México 37%). Adjusting for age, BMI, height loss, steroid use and physical activity, the OR for presenting OA is 6.45 (p<0.001) in women over 80 compared to those 50–59 Conclusions: Radiographic OA is highly prevalent in Latin American women over 50 and associated with progressing age and BMI. Brazil has the highest prevalence of OA. Disclosure of Interest: None declared